Avaliação da atenção primária à saúde de crianças no município de Joanópolis, São Paulo, Brasil - Ponnet, Liz [UNIFESP] (2016)
This study evaluated Primary Health Care services that children aged 0 to 12 used in a small city, the Municipality of Joanopolis, in the State of São Paulo, from the point of view of the legal responsibles and of the health professionals. The interviewed legal responsibles (the parents) evaluate the health services for their children as 5,62/10 (General Primary Health Care Score), which is lower than the established cut-off point of 6,60. The parents refer they are unsatisfied with the attributes of accessibility, long-term person care, integrated care- provided services, family and community oriented care. If we consider the Essential Primary Health Care Score the mean is 6,92. The interviewed health professionals consider the services as inadequate: the General Score for PHC is 5,52 and the Essential Score is 5,67. The only attribute they consider adequate is accessibility. There is a discrepancy between the scores the parents and the health professionals attribute to the accessibility of health services for children in Joanopolis. The actual study results, in a small city, are comparable with the results from published studies in big urban centers: in both scenarios the family and community oriented care is considered inadequate, which leads us to the question about what kind of PHC we are talking in Brazil. This research studied the dimension of access to health services in details. It was observed that almost a third of the studied children live in rural zone areas: even with an existing geographic barrier the rural children were able to access the PHC-services in this study. Children of all age ranges were able to access PHC-services in this study: the normal distribution of the age of the studied children is an indicator of access to health services, even if the realized access was studied. The parents living in rural areas consider the quality of provided services less times as “very good” compared with parents living in urban areas (P value <0,001). The study also showed that carrying out an evaluation of used Primary Health Care services using the PCATool-Brasil in this small rural city needed an investment of 1.241 working hours (and corresponding budget), as well as motivated health professionals and managers to perform the study